Comparative Hematology, Morphology and Ultrastructure of Blood Cells in Monocellate Cobra (Naja kaouthia), Siamese Spitting Cobra (Naja siamensis) and Golden Spitting Cobra (Naja sumatrana) - Chaleow Salakij; Jarernsak Salakij; Lawan Chanhome (Agriculture and Natural Resources, 2002)
Blood samples of 17 monocellate cobras (Naja kaouthia), 12 Siamese spitting cobras (Naja siamensis) and 6 golden spitting cobras (Naja sumatrana) in the Queen Saovabha Memorial Institute were collected from ventral caudal vein for basic hematology, light microscopic, scanning and transmission electron microscopic features of blood cells. There was no hematozoa detected in all monocellate cobras. Five Siamese spitting cobras (42%) and four golden spitting cobras (74%) were positive for Hepatozoon sp. Lymphocytes were the most commonly observed leukocytes in all cobras and average 6-8 μm in diameter. Azurophils were the second most commonly observed leukocytes, averaging 10-17 μm in diameter. Azurophils in golden spitting cobra contained more number of azurophilic granules and ribosomes than the other cobras. Heterophils were the largest leukocytes, averaging 16-19 μm in diameter. Eosinophils in monocellate cobras revealed large bulging granules and usually were medium-sized cells, averaging 10-14 μm in diameter. Eosinophils in Siamese spitting cobra were larger than those in monocellate cobra but contained smaller granules. Eosinophils in golden spitting cobra showed bulging granules but smaller than those in monocellate cobra. Basophils in all kind of cobras were similar and as small as lymphocyte but revealed many small granules polarity. Scanning electron microscopic examination revealed the surface of thrombocytes, erythrocytes, lymphocyte, azurophil and heterophil in monocellate cobra. Transmission electron microscopic examination showed organelles within azurophil and thrombocyte of Siamese spitting cobra and azurophis and gamonts of Hepatozoon sp. in erythrocytes of golden spitting cobra.